(untitled) (Journal of Educational Data Mining, 2026)
This issue features three regular articles and one article selected by the Journal Track editors for EDM 2025. The JEDM Track received 15 submissions, three of which reached the final stage in time for publication in the previous issue, with a fourth appearing here. The editorial also acknowledges the reviewers who contributed feedback on these articles.